Dimerization propensity of the β 1 -adrenergic receptor in lipid nanodiscs probed by DEER and single-molecule spectroscopies - Nina Kubatova; Thomas Schmidt; Quan Wang; G. Marius Clore (Proceedings of the National Academy of Sciences, 2025)
G protein–coupled receptors (GPCRs) comprise a large class of membrane proteins that mediate cellular responses to a wide range of external signals and as such constitute major drug targets. While oligomerization has been shown to play a well-established role in modulating signaling for class C GPCRs (e.g., the glutamate and GABA receptors), the functional relevance of oligomerization for class A receptors, such as the β 1 -adrenergic receptor (β 1 AR), remains unclear. Here, we have examined the influence of the membrane mimetic environment on the dimerization propensity of β 1 AR using a combination of pulsed Q-band double electron–electron resonance spectroscopy and single-molecule fluorescence brightness measurements in an Anti-Brownian Elektrokinetic trap. While β 1 AR is predominantly monomeric in docecyl-β-D-maltoside (DDM) micelles, reconstitution of β 1 AR in lipid nanodiscs preferentially favors symmetric parallel dimers. Using nanodiscs of different diameters we observed a clear size-dependent increase in the dimer fraction, reaching over 50% of the β 1 AR molecules in large (~12.5 nm diameter) nanodiscs. Addition of cholesteryl hemisuccinate, an analog of cholesterol, suppresses β 1 AR dimerization in lipid nanodiscs, recapitulating the behavior in DDM micelles. This work provides quantitative evidence that β 1 AR possesses an intrinsic, membrane sensitive predisposition for dimerization, and highlights the importance of spatial membrane constraints in the modulation of class A GPCR dimerization.